Constructing a labor exodus a critical discourse analysis of the presidential discourses on labor migration in the Labor Day speeches from 1974-2016 - Aseo, Knulp Dalmero 1997-; Martelino, Meghan Therese (2018)
Presidential discourses on labor migration in the Labor Day speeches of Philippine Presidents from Ferdinand Marcos to Benigno Aquino III are worthy of scrutiny and analysis. This is because these discourses are opportunities for the Presidents to directly address the issues facing many Filipino laborers, including Filipino migrant workers. This study looked at how discourses are formed, shaped and (re)negotiated by the Philippine Presidents in the Labor Day speeches over time. It is theoretically anchored on Fairclough's Critical Discourse Analysis, supplemented by Entman's Framing Theory, and Jessop's Cultural Political Economy approach. Using a qualitative approach, the researchers employed textual analysis to thematize, describe and analyze the statements from the studied speeches. Results showed that Presidents tend to shift the discourse on labor migration during their presidencies depending on the crisis situations they are facing, as well as the general policy goals they hope to achieve. Despite the constant change in discourse, however, some discourses remained across the forty years. The constant change may be due to the power of the Presidential discourse to minimize the accommodation of the dissenting voices and therefore monopolize the direction of the policies relating to labor migration."